The Effect of Sizes of the Cast Polyamide 6 Rods upon Tensile-Impact Strength - Odrobina, Miklós; Kalácska, Gábor; Keresztes, Róbert (International Journal of Engineering and Management Sciences, 2018)
We have studied the tensile-impact strength of the magnesium catalysed cast polyamide 6 (PA6) rods according to the EN ISO 8256:2004 standard. The purpose of our investigation was to follow: the mechanical properties of rods are mapped beside same casting technological process in case of different diameters. We have compared the received results with each other than have sought disparities. We examined cylindrical product (rod) in seven dimensional steps in diameter ranging from 40 mm to 300 mm. We have determined that the semi-finished products can be divided into two groups typically in case of their tensile-impact strengths in this size range. The tensile-impact strength is higher in case of the rods with a diameter of less than 100 mm and it is smaller in the larger dimension range. Therefore, the smallest tensile-impact strength can be established in case of the natural semifinished PA6 rods that each rod accomplishes independently of size. However, a range can be determined, which the tensile-impact strength values of product are separated according to the manufacturing size